2022
DOI: 10.1088/2040-8986/ac5476
|View full text |Cite
|
Sign up to set email alerts
|

Propagation-invariant high-dimensional orbital angular momentum states

Abstract: Photonic states encoded in spatial modes of paraxial light fields provide a promising platform for high-dimensional quantum information protocols and related studies, where several pioneering theoretical and experimental demonstrations have paved the path for future technologies. Crucially, critical issues encountered in free-space propagation still represent a major challenge. This is the case of asynchronous diffraction between spatial modes with different modal orders, which experience variations in their t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…[25,26] Importantly, this commonly used technique requires a precise priori knowledge of some of the parameters of the unknown beam, such as its initial beam width radius w 0 and its radius of curvature R z , for an accurate characterization of the mode in question. [27][28][29] For ultrashort pulses, transverse dispersion induced by the grating of complex-amplitude modulation would bring additional issues. Although a recent work has suggested that one can measure OAM of intense ultrashort pulses by exploiting strong-field ionization, [30] a simple technique towards commercial uses has not been developed.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] Importantly, this commonly used technique requires a precise priori knowledge of some of the parameters of the unknown beam, such as its initial beam width radius w 0 and its radius of curvature R z , for an accurate characterization of the mode in question. [27][28][29] For ultrashort pulses, transverse dispersion induced by the grating of complex-amplitude modulation would bring additional issues. Although a recent work has suggested that one can measure OAM of intense ultrashort pulses by exploiting strong-field ionization, [30] a simple technique towards commercial uses has not been developed.…”
Section: Introductionmentioning
confidence: 99%